Capillary ion electrophoresis–capacitively coupled contactless conductivity detection of inorganic cations in human saliva on a polyvinyl alcohol-coated capillary - Mori, Masanobu; Kaseda, Maki; Yamamoto, Tsukasa; Yamada, Sachiko; Itabashi, Hideyuki (Analytical and bioanalytical chemistry, 2012)
Capillary ion electrophoresis–capacitively coupled contactless conductivity detection (CIE-C4D) with a polyvinyl alcohol chemically coated capillary (PVA capillary) was used to analyze inorganic cations (Na + , K + , NH 4 + , Mg 2+ , and Ca 2+ ) commonly found in human saliva. The PVA capillary, which was made by our laboratory, minimized electro-osmotic flow in the wide pH range of the background electrolyte (BGE), and the PVA layer adsorbed to capillary wall did not affect the conductimetric background level. In this study, we determined an optimized BGE of 30 mM lactic acid/histidine plus 3 mM 18-crown-6 for the CIE-C4D system using the PVA capillary, which could simultaneously improve the separation of Mg 2+ and Ca 2+ from Na + and that of K + from NH 4 + . This system obtained highly reproducible separation of cations in human saliva samples within 8 min at 20 kV without deprotonation. The quantifiability of cations in human saliva samples on the CIE-C4D system was demonstrated through identification by ion chromatography with satisfactory results.